Strategi Komunikasi Dalam Experiential Marketing Guna Menjaga Loyalitas Pengunjung Desa Wisata Buatan - Zein, Faras Iqlima; Purnamasari, Devi (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
Companies need innovation to sell their products. Apart from the quality of the product, experience is also required to arouse enthusiasm for the product among the public. Managers of tourist attractions need experiential marketing as a way to avoid being drowned out by new competitors. For companies that have implemented experiential marketing methods such as Dusun Semilir, it will remain a tourist attraction that is still popular with the public. Dusun Semilir was the first to discover new ride innovations such as colorful slides. Considering that this slide is popular with many people and has gone viral, of course, many tourist attractions are starting to build similar rides and will build them better than the inventor. This is a big challenge for Dusun Semilir so visitors still choose to enjoy the rides at Dusun Semilir even though the rides are similar to rides from other tourist attractions. This experiential marketing will help tourist attractions such as Dusun Semilir so that visitors remain loyal to visiting Dusun Semilir and feel satisfied with the Dusun Semilir tourist attraction.